2021
DOI: 10.1155/2021/5520581
|View full text |Cite
|
Sign up to set email alerts
|

A Review Leveraging a Rare and Unusual Case of Basal Cell Carcinoma of the Prostate

Abstract: Basal cell carcinoma (BCC) is a rare nonacinar variant of prostatic carcinoma. In spite of prostatic acinar adenocarcinoma being one of the most common carcinomas in prostate, <100 prostatic BCC cases have been reported to date. Adenoid cystic/cribriform histology has been described in varying proportions to occur in prostatic BCC and is reported to be associated with aggressive behavior and high risk of metastasis. Herein, we present a case of prostatic BCC with adenoid cystic morphology, comprehensively d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…BCC of the prostate metastasizes most commonly in visceral organs (liver, lungs), rarely in bones. 4 In our case, the tumor was limited to the prostate and bladder. During the follow-up after six months, there was an enlarged lymph node in the right iliac fossa.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…BCC of the prostate metastasizes most commonly in visceral organs (liver, lungs), rarely in bones. 4 In our case, the tumor was limited to the prostate and bladder. During the follow-up after six months, there was an enlarged lymph node in the right iliac fossa.…”
Section: Discussionmentioning
confidence: 57%
“…The first case of prostatic BCC was published in 1974; to date, there are no more than 150 cases reported in the literature. 3 , 4 Usually, it is detected in patients aged 50 to 70 years, mostly arises in the transitory zone and the patients present with nocturia, urgency and urinary obstruction. 3 , 5 , 6 PSA is usually not elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 89% of patients with BCCP initially present with predominantly obstructive lower urinary tract symptoms, while others present with hematuria ( 8 ). The serum PSA levels are usually within normal limits, which results in its misdiagnosis as prostatic hyperplasia ( 12 ). Its diagnosis is often confirmed by histopathological examination after transurethral resection of the prostate ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other markers such as CD44 and P53 may also be useful in the diagnosis of prostate basal cell carcinoma, but the results are inconsistent ( 8 ). The strong expression of Bcl-2 and increased Ki-67, which are associated with the grade of malignant tumors, help to distinguish it from benign basal cell hyperplasia ( 8 , 12 ). There is typically no PSA or PAP immunostaining in BCCP ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been consistently documented that prostate basal cell carcinoma is very rare, accounting for only about 0.01% of the total prostate malignancies 69 - 73 , which strongly suggests that the prostate basal cell population is very unlikely to be a major target of the prostate carcinogenesis. However, it has also been consistently demonstrated that the PBCL belongs to a self-renewal cell population 74 - 80 . For this and other reasons, the PBCL population itself also frequently suffers from a variety of degeneration- and regeneration-related pathologic alterations that includes, but is not limited to the following:…”
Section: The Pbcl Itself Is the Target Of A Variety Of Pathologic Alt...mentioning
confidence: 97%